2020
DOI: 10.1007/s42452-020-3055-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-label classification of line chart images using convolutional neural networks

Abstract: In this paper, we propose a new convolutional neural network (CNN) architecture to build a multi-label classifier that categorizes line chart images according to their characteristics. The class labels are organized in the form of trend property (increasing or decreasing) and functional property (linear or exponential). In the proposed method, the Canny edge detection technique is applied as a data preprocessing step to increase both the classification accuracy and training speed. In addition, two different mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The line and bar charts are the most researched. Kosmen et al [16] created a CNN architecture that can classify line charts according to trend property (increasing or decreasing) and functional property (linear or exponential). The achieved average classification accuracy is 93.76%.…”
Section: Related Workmentioning
confidence: 99%
“…The line and bar charts are the most researched. Kosmen et al [16] created a CNN architecture that can classify line charts according to trend property (increasing or decreasing) and functional property (linear or exponential). The achieved average classification accuracy is 93.76%.…”
Section: Related Workmentioning
confidence: 99%
“…Label powerset transforms MDC problems into multi-class classification problems by combining all unique class labels in the training set as a new single label [43]. As a result of this process, each instance in the training set has only one target attribute with one class label.…”
Section: Label Powersetmentioning
confidence: 99%
“…Chagas et al [ 28 ] compared listed methods and showed that CNNs outperform by roughly 20%. Publications by Bajić and Job [ 11 ], Kosemen and Birant [ 29 ], Ishihara et al [ 30 ], and Dadhich et al [ 31 ] use custom CNN architectures for chart-type classification. CNNs can also be used out-of-the-box; some are available as pre-trained models.…”
Section: Related Workmentioning
confidence: 99%